Green process for chlorine-free benzaldehyde from the solvent-free oxidation of benzyl alcohol with molecular oxygen over a supported nano-size gold catalyst - Choudhary, Vasant R.; Dhar, A.; Jana, Prabhas; Jha, Rani; Uphade, B. S. (Green Chemistry, 2005)
Benzyl alcohol is oxidized selectively to benzaldehyde with high yield, with a little formation of benzylbenzoate, by molecular oxygen over a reusable nano-size gold catalyst supported on U3O8, MgO, Al2O3 or ZrO2 in the absence of any solvent.

GaClx- or GaAlClx-grafted Si-MCM-41: highly active and moisture insensitive/stable catalyst for the acylation and benzylation of benzene, naphthalene and substituted benzenes - Choudhary, Vasant R.; Jha, Rani (Applied Catalysis A-General, 2007)
GaClx- and GaAlClx-grafted Si-MCM-41 catalysts were prepared by reacting anhydrous GaCl3 and mixed anhydrous GaCl3 and AlCl3, respectively, with the terminal hydroxyl groups of Si-MCM-41 (pore size: 2.5 nm) in a dry non-aqueous reaction medium (CCl4) under reflux. The catalysts showed high activity for both the acylation and benzylation (with benzoyl chloride and benzyl chloride, respectively) of benzene, toluene, p-xylene, cumene, mesitylene, anisole and naphthalene. Both the catalysts are moisture insensitive or less moisture sensitive; the presence of moisture has a beneficial effect in the acylation over both the catalysts. The catalytically active sites of the GaClx-grafted Si-MCM-41 are (-O-)(2)GaCl (i.e. partially chlorided Ga anchored to Si through -O- linkage) species and the equivalent sites of the GaAlClx-grafted Si-MCM-41 are (-O-)(2)Ga(or Al)Cl and (-O-)(3)Ga(or Al) species. The high acylation/benzylation activities of both the catalysts even in the presence of moisture are attributed to their redox properties (Ga3+ -> Ga1+) rather than to their Lewis acid properties. After the grafting/chemical bonding, the grafted gallium chloride catalyst showed much higher acylation activity but lower benzylation activity than the physically deposited (on Si-MCM-41) or unsupported GaCl3. The GaAlClx-grafted Si-MCM-41 showed higher acylation activity than the GaClx-grafted Si-MCM-41, due to a synergetic effect of the Ga and Al species. However, the relative benzylation activity of the two catalysts showed strong dependence upon the presence or absence of electron donating group(s) and also upon the electron donating ability of the group(s) attached to the aromatic nucleus. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: acylation benzylation; GaAlClx-grafted Si-MCM-41; GaClx-grafted Si-MCM-41; moisture insensitive

GaAlCl(x)-grafted Mont.K-10 clay: highly active and stable solid catalyst for the friedel-crafts type benzylation and acylation reactions - Choudhary, Vasant R.; Jha, Rani (Catalysis Communications, 2008)
A liquid phase reaction of anhydrous GaCl(3) and AlCl(3) with the surface hydroxyl groups (with HCl evolution) of Mont. K-10 clay in dry CCL(4) under reflux resulted in a novel GaAlCl(x),-grafted Mont.K-10 catalyst [with Cl/(Ga + Al) = 1]. The catalyst showed high activity and stability in the Freidel-Crafts type benzylation and benzoylation (by benzyl chloride and benzoyl chloride, respectively) of benzene, naphthalene and substituted benzenes, even in the presence of moisture. It also showed good activity for the benzoylation of nitrobenzene (i.e. even in the presence of strong electron withdrawing group, like nitro group, attached to the benzene ring). The catalytically active surface species in the catalyst are -(O)(2)-Ga(or Al)Cl. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: benzoylation of aromatics; benzylation of aromatics; GaAlCl(x)-grafted Mont.K-10